Home Environment as a Source of Life-Threatening Azole-Resistant Aspergillus fumigatus in Immunocompromised Patients. (28th September 2016) - Lavergne, Rose-Anne; Chouaki, Taieb; Hagen, Ferry; Toublanc, Bénédicte; Dupont, Hervé; Jounieaux, Vincent; Meis, Jacques F.; Morio, Florent; Le Pape, Patrice
Abstract : A case of fatal aspergillosis due to a TR46 /Y121F/T289A azole-resistant Aspergillus fumigatus is reported. Environmental investigations at the patient's residence led to the recovery of TR46 /Y121F/T289A isolates, genotypically indistinguishable from the clinical isolate, supporting for the first time the direct role of household as potential source of azole-resistant invasive aspergillosis.